Did COVID-19 Make Me an Afro-Pessimist? A Conversation in Three Parts. (14th October 2022) - Kwakye, Chamara Jewel; Millward, Jessica
Abstract : As the COVID-19 pandemic continues to rage and disproportionately affect BIPOC, we keep count of the death toll around the world, in the U.S., in our own communities and in our own families. How can we have a "wish to live, " while so many around us die? Does a space exist between fateful (faithful) optimism present in Aretha Franklin's, "Mary Don't You Weep?" and the ever-present power structure, that as Reverend Al Sharpton noted, has always had its knee on our necks? More concretely, how do we reconcile what Aisha Durham discusses as "weathering and wounded, " as we sit in the space of being both and not wanting to endure much more. This piece articulates some of the conversations that we have stumbled upon, worked through and raged against from the space of our collective homes and fatigued spirits. It addresses notions of Afro-Pessimism and the intersection of Black Feminist Theory, the role that grief plays in Black Feminist praxis, the role of Diaspora in the historical imagination, and asks the question, "Did COVID and the state-sanctioned killings of Black people make us Afro-Pessimists?"